2008
DOI: 10.1086/595588
|View full text |Cite
|
Sign up to set email alerts
|

Do All Flares Have White-Light Emission?

Abstract: High-cadence, multiwavelength optical observations of a solar active region (NOAA 10969), obtained with the Swedish Solar Telescope, are presented. Difference imaging of white light continuum data reveals a white light brightening, 2 min in duration, linked to a co-temporal and co-spatial C2.0 flare event. The flare kernel observed in the white light images has a diameter of 300 km, thus rendering it below the resolution limit of most space-based telescopes. Continuum emission is present only during the impuls… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 31 publications
(36 reference statements)
6
102
2
Order By: Relevance
“…Gamma rays typically accompany HXR when detectable (e.g., Cliver et al 1994;Shih et al 2009) Matthews et al 2003;Hudson et al 2006;Wang 2009) make it possible to detect much weaker and therefore more numerous events. Hudson et al (2006) report a GOES C1.3 event observed by TRACE, and Jess et al (2008) found a GOES C2.0 event even with ground-based observations.…”
Section: Flare Morphologymentioning
confidence: 89%
“…Gamma rays typically accompany HXR when detectable (e.g., Cliver et al 1994;Shih et al 2009) Matthews et al 2003;Hudson et al 2006;Wang 2009) make it possible to detect much weaker and therefore more numerous events. Hudson et al (2006) report a GOES C1.3 event observed by TRACE, and Jess et al (2008) found a GOES C2.0 event even with ground-based observations.…”
Section: Flare Morphologymentioning
confidence: 89%
“…As our study does not include microflares (i.e., GOES C class and smaller), we cannot state anything regarding this group of events. Nevertheless, WL emission has been reported from C-class flares (Jess et al 2008) and there are GOES A-and B-class flares with relatively intense HXR emissions (of the order of 0.1 photon s Ishikawa et al 2011) for which WL emission could potentially be detectable.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the TRACE WL/ultraviolet (UV) emission always has a higher contrast than that of the traditional WLFs and the observations are sometimes saturated, it is unclear whether the TRACE continuum is affected by UV emission. Jess et al (2008) used high resolution observations of the one-meter Swedish Solar Telescope to detect WL emission in the blue continuum around 3954 Å with a peak intensity 300% above the quiescent flux in a C2.0 flare. This high emission contrast, although restricted to a small area, is surprising and it remains to be verified whether it is a common feature in WLF observations.…”
Section: Introductionmentioning
confidence: 99%